Drug Physicochemical Properties and Capsule Fill Determine Extent of Premature Gastric Release from Enteric Capsules - Fouad S. Moghrabi; Hala M. Fadda (MDPI AG, 2022)
Intrinsically, enteric capsule shells offer several advantages compared to coating of dosage forms with enteric polymers. We undertook a systematic investigation to elucidate capsule-fill parameters that may result in premature gastric drug release from Vcaps® Enteric capsules (Lonza CHI, Morristown, NJ, USA). Four model drugs with different ionization and solubility profiles were investigated: acetaminophen, ketoprofen, trimethoprim and atenolol. Different fill loads, diluents and drug-to-diluent ratios were explored. Enteric capsules were filled with drug or drug and diluent powder mix and underwent USP II dissolution testing using mini-vessels and paddles. Capsules were tested in pH 2 (0.01 M HCl) or pH 4.5 (3.2 × 10−5 M HCl) 200 mL acid media to simulate normal, fasted or hypochlorhydric gastric pH, respectively. Acetaminophen, trimethoprim and atenolol displayed premature gastric drug release from enteric capsules. The extent of premature release was dependent on drug solubility, ionization profile and capsule-fill level. At 100 mg drug-fill level, acetaminophen, trimethoprim and atenolol gave rise to 10.6, 12.2 and 83.1% drug release, respectively, in normal, fasted, gastric fluids. Diffusion layer pH of trimethoprim and atenolol in pH 2 media was determined to be pH 6.3 and 10.3, respectively. Upon increasing capsule-fill load using microcrystalline cellulose as a diluent, a significant reduction in premature gastric release was observed. However, including mannitol as a diluent was only effective at decreasing premature drug release at a low drug-to-diluent ratio. Systematic in vitro screening of enteric capsule fills needs to be conducted to ensure that drug product performance is not compromised.